2019
DOI: 10.1242/jcs.232306
|View full text |Cite
|
Sign up to set email alerts
|

Kinesin-8 and Dis1/TOG collaborate to limit spindle elongation from prophase to anaphase A for proper chromosome segregation in fission yeast

Abstract: High-fidelity chromosome segregation relies on proper microtubule regulation. Kinesin-8 has been shown to destabilise microtubules to reduce metaphase spindle length and chromosome movements in multiple species. XMAP215/chTOG polymerases catalyse microtubule growth for spindle assembly, elongation and kinetochore-microtubule attachment. Understanding of their biochemical activity has advanced, but little work directly addresses the functionality and interplay of these conserved factors. We utilised the synthet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 89 publications
0
25
0
Order By: Relevance
“…For instance, during the first meiotic division, Dis1 plays a role in microtubule shortening to pull kinetochores polewards: this protein appears to promote MT depolymerisation under this condition [26]. In addition, we recently showed that Dis1 potentiates spindle shortening in the absence of the Klp5-Klp6 kinesin-8 complex to ensure kinetochore capture by spindle MTs for proper mitotic progression [27]. Furthermore, Dis1, but not Alp14, plays a role in epigenetic regulation at centromeric chromatin [55].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, during the first meiotic division, Dis1 plays a role in microtubule shortening to pull kinetochores polewards: this protein appears to promote MT depolymerisation under this condition [26]. In addition, we recently showed that Dis1 potentiates spindle shortening in the absence of the Klp5-Klp6 kinesin-8 complex to ensure kinetochore capture by spindle MTs for proper mitotic progression [27]. Furthermore, Dis1, but not Alp14, plays a role in epigenetic regulation at centromeric chromatin [55].…”
Section: Discussionmentioning
confidence: 99%
“…Most of klp6Δ SPB-dependent spindles segregate parental chromosomes into two masses (84%), although a minority exhibits three to six masses, consistent with chromosome segregation defects intrinsic to the loss of Klp5/6 (Fig. 7 G, n=69) (Pinder et al, 2019; Syrovatkina et al, 2013; Garcia et al, 2002; West et al, 2001). Self-assembled spindles present severe segregation defects: nearly a third (32%) of the spindles do not segregate chromosomes, leaving the parental nucleus as a single mass, while another third (36%) segregate chromosomes up to three to six masses and only a minority (32%) segregates into two masses i.e., normal segregation (Fig.…”
Section: Resultsmentioning
confidence: 54%
“…7 B, 20’ arrowhead, 70’ top arrowhead) as well as lagging chromosomes (Fig. 7 B, 70’ bottom arrowhead) (Pinder et al, 2019; Syrovatkina et al, 2013). Remarkably, in the case of self-assembled spindles, deletion of Klp6 rendered MI and MII self-assembled spindles thicker and brighter respect to klp6 + (compare Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Whether or not Dis1 could also promote MT nucleation remains to be determined. By contrast, we and others have recently shown that Dis1 is capable of promoting MT depolymerisation, rather than polymerisation, under some physiological circumstances [26,27].…”
Section: Introductionmentioning
confidence: 68%
“…For instance, during the first meiotic division, Dis1 plays a role in microtubule shortening to pull kinetochores polewards: this protein appears to promote MT depolymerisation under this condition [26]. In addition, we recently showed that Dis1 potentiates spindle shortening in the absence of the Klp5-Klp6 kinesin-8 complex to ensure kinetochore capture by spindle MTs for proper mitotic progression [27]. Furthermore, Dis1, but not Alp14, plays a role in epigenetic regulation at centromeric chromatin [56].…”
Section: Discussionmentioning
confidence: 99%